El amor en los tiempos del cólera - García Márquez, Gabriel, 1927-2014 (Vintage español, 2003)
The story of a fantastic wedding, the return of the bride to her parents in disgrace, her brothers' resolve to seek revenge on her corruptor, and the townspeoples' refusal to depart from routine.